A Challenging Classic Coupling: Esterification of Camphoric Acid - a Steric - Hindered Polar Carboxylic Acid and Solanesol - a Long - Chain Nonpolar Alcohol. - Phung, Nhu Hoa (H. : ĐHQGHN, 2018)
tr. 220-227